1990
DOI: 10.1001/archotol.1990.01870050090013
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Cefaclor vs Amoxicillin on Recovery After Tonsillectomy in Children

Abstract: Tonsillectomy and adenoidectomy continues to be one of the most commonly performed operations in the pediatric age group. The morbidity from tonsillectomy can be severe and includes throat and ear pain, fever, lethargy, and poor oral intake. A previous study at the Children's Hospital of Philadelphia (Pa) demonstrated the efficacy of amoxicillin therapy in minimizing some of these postoperative symptoms. However, some children continue to have a prolonged recovery even while receiving this antibiotic regimen. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 5 publications
0
11
0
1
Order By: Relevance
“…Although these studies may have been useful in providing additional background information, they would not have been specifically useful for both, the qualitative and quantitative portions of this meta-analysis. On further review of the remaining 18 articles, 7 were withdrawn due to a lack of data regarding the primary clinical outcome of interest [9][10][11][12][13][14][15], and 5 were withdrawn due to the absence of a control 856 S. Iyer et al [16][17][18][19][20]. The seven remaining studies with usable information on post-operative outcomes of interest were included in the qualitative portion of this meta-analysis [21][22][23][24][25][26][27].…”
Section: Trial Flowmentioning
confidence: 99%
“…Although these studies may have been useful in providing additional background information, they would not have been specifically useful for both, the qualitative and quantitative portions of this meta-analysis. On further review of the remaining 18 articles, 7 were withdrawn due to a lack of data regarding the primary clinical outcome of interest [9][10][11][12][13][14][15], and 5 were withdrawn due to the absence of a control 856 S. Iyer et al [16][17][18][19][20]. The seven remaining studies with usable information on post-operative outcomes of interest were included in the qualitative portion of this meta-analysis [21][22][23][24][25][26][27].…”
Section: Trial Flowmentioning
confidence: 99%
“…Adenotonsillectomy still remains as one of the most frequent surgical procedures done in the pediatric population 2 . Morbidity in the post-op is mostly due to pain, fever, vomiting, bleeding, and fatigue, to name a few 5 .…”
Section: Discussionmentioning
confidence: 99%
“…1,2 In the early 20th century this was a procedure medical doctors often resorted to, regardless of how minimally symptomatic patients were. Since the 1960s, however, there was marked progress in immunology and increased knowledge on the physiology and relevance of the Waldeyer's ring, which led to a review of the established indications for surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Still in this study, 17 to 20% of the species of Haemophilus produced ß-lactamase. 14 Based on these facts, Mevio et al concluded that amoxicillin-clavulanate would be the most effective antimicrobial drug to eradicate such microorganisms, and his opinion is also shared by Grandis et al and others. 3,4 Additionally, this type of coverage would act in anaerobic organisms that are also present in this site.…”
Section: Literature Reviewmentioning
confidence: 96%